The effect of indirect veneering materials as light interpose on microhardness of dual cured resin cements - Maha A AL-Murad; Ma'an M Nayif (University of Mosul, College of Dentistry, 2013)
Aims: The aim of this study was to investigate the influence of different indirect veneering materials on the microhardness of dual-cured resin cements. Materials and Methods: Three disc specimens (2.0 mm height and 5mm diameter)were prepared from the following indirect restorative materials (Indirect composite resin, Gardia-GC, JAPAN, Feldspathic porcelain VITA VIMK 95-Germany and Zirconia veneer, VITA-Zahnfabrik, Germany). Two dual cure resin cements were used ( Variolink II, Ivoclar Vivadent AG, Liechtenstein and Bis-Cem, Bisco-Schaumburg, USA). Twenty specimens were prepared from each type of cement and divided into 4 groups, one as control and others as indirect restorative materials. After mixing cements were placed in a plastic mold (5mm diameter and 1mm height ) and light activated directly or through veneering discs for 30s using LED light at 500mW/cm2. Specimen subjected to three indentation using Vicker hardness tester with load of 50gm for 15 second. Data were statistically analyzed using ANOVA and independent t-test at (α= 0.05). Results: For both cements the control groups showed higher hardness value than other groups. Specimens cured through indirect resin composite shows the highest microhardness while those cured through Zirconia shows the lowest value. Variolink II resin cement demonstrated higher microhardness than Bis-Cem cement regardless of the curing condition. Conclusions: Type of indirect restorative veneering materials influence microhardness of resin cement luting agent